A Dual Pathway of Governmental Support for SME Performance: Paradoxical Impact of Organizational Learning Capabilities - Do, Ngoc Bich; Nguyen, Hue Minh; Do, Hai-Ninh; Nguyen, Kim Thao; Nguyen, Tra My (Journal of Applied Data Sciences, 2026)
Purpose: The Global market is creating rising tensions and uncertainty for businesses, especially for Small and Medium Enterprises (SMEs). which must be addressed by the government. Despite the critical role of technological innovation, significant economic hurdles for SMEs remain. This research explores the mechanism by which government support contributes to SMEs' performance through technological innovation, and further examines the moderating role of Organizational Learning Capabilities (OLC). Design/methodology/approach: A quantitative method was adopted using SPSS and SmartPLS 4.0 software to evaluate the research model. Data was collected through a survey-based questionnaire completed by leaders and senior managers representing 450 Vietnamese SMEs. Findings: Analytical results reveal that government support exerts a significant direct influence on SME performance, while its effects are partially transmitted through technological innovation, indicating a dual pathway that enhances overall outcomes. Interestingly, the moderating role of organizational learning capability is confirmed. Specifically, it strengthens the translation of government support into technological innovation but simultaneously weakens the positive association between technological innovation and SME performance. Implications: SME managers in developing countries should prioritize innovation-focused as phase one, followed by market-focused in phase two to capture the support of governments. Furthermore, SMEs also prepare resource slack for past reflection and analyze gaps between innovation practices and financial returns to provide real-time modifications to reduce negative outcomes from OLC.